Root suckering in Dichrostachys cinerea and a comparison of subspecies africana and nyassana - Wakeling, Julia (Department of Biological Sciences, 2017)
Clonal growth has been studied little in Africa, and models of savanna tree-grass interactions have not included vegetatively reproducing trees or shrubs. Root suckering has been observed in both subspecies of Dichrostachys cinerea that occur in Southern Africa. This study, performed in Hluhluwe-iMfolozi Game Reserve, KwaZulu Natal South Africa, examines variability in subspecies distribution and the extent of root suckering under different fire regimes, and levels of herbivory. Variations in subspecies distribution are clear. Subspecies africana, with greater structural defenses, survives in areas of high herbivory but is rarely seen under high fire disturbance. The opposite is true for subspecies nyassana, which is poorly defended against herbivory. There was no difference in vegetative propogation by root suckering in areas of different fire regime, rainfall, soil type or degree of herbivory. The implication is that the management of the species will be a formidable task. A combination of burning during summer, when below ground reserves are depleted, and heavy browsing may aid in the control of this species.